Artemether-Lumefantrine Versus Chloroquine for the Treatment of Uncomplicated Plasmodium knowlesi Malaria: An Open-Label Randomized Controlled Trial CAN KNOW. (23rd October 2017) - Grigg, Matthew J; William, Timothy; Barber, Bridget E; Rajahram, Giri S; Menon, Jayaram; Schimann, Emma; Wilkes, Christopher S; Patel, Kaajal; Chandna, Arjun; Price, Ric N; Yeo, Tsin W; Anstey, Nicholas M
Abstract : AL is highly efficacious for treating uncomplicated Plasmodium knowlesi malaria; its excellent tolerability and rapid therapeutic response allowed earlier hospital discharge, and support its use as a first-line artemisinin-combination therapy treatment policy for all Plasmodium species in Malaysia. Abstract: Background: Plasmodium knowlesi is reported increasingly across Southeast Asia and is the most common cause of malaria in Malaysia. No randomized trials have assessed the comparative efficacy of artemether-lumefantrine (AL) for knowlesi malaria. Methods: A randomized controlled trial was conducted in 3 district hospitals in Sabah, Malaysia to compare the efficacy of AL against chloroquine (CQ) for uncomplicated knowlesi malaria. Participants were included if they weighed >10 kg, had a parasitemia count <20000/μL, and had a negative rapid diagnostic test result for Plasmodium falciparum histidine-rich protein 2. Diagnosis was confirmed by means of polymerase chain reaction. Patients were block randomized to AL (total target dose, 12 mg/kg for artemether and 60 mg/kg for lumefantrine) or CQ (25 mg/kg). The primary outcome was parasite clearance at 24 hours in a modified intention-to-treat analysis. Results: From November 2014 to January 2016, a total of 123 patients (including 18 children) were enrolled. At 24 hours after treatment 76% of patients administered AL (95% confidence interval [CI], 63%–86%; 44 of 58) were aparasitemic, compared with 60% administered CQ (47%–72%; 39 of 65; risk ratio, 1.3 [95% CI, 1.0–1.6]; P = .06). Overall parasite clearance was shorter after AL than after CQ (median, 18 vs 24 hours, respectively; P = .02), with all patients aparasitemic by 48 hours. By day 42 there were no treatment failures. The risk of anemia during follow-up was similar between arms. Patients treated with AL would require lower bed occupancy than those treated with CQ (2414 vs 2800 days per 1000 patients; incidence rate ratio, 0.86 [95% CI, .82–.91]; P < .001). There were no serious adverse events. Conclusions: AL is highly efficacious for treating uncomplicated knowlesi malaria; its excellent tolerability and rapid therapeutic response allow earlier hospital discharge, and support its use as a first-line artemisinin-combination treatment policy for all Plasmodium species in Malaysia. Clinical trials registration: NCT02001012.